Dupilumab Efficacy and Safety as an Add-On Therapy in Uncontrolled Asthma Patients: A Systematic Review - Evelyn Evelyn; Putra Brillian Djohan; Fauna Herawati (Universitas Nahdlatul Ulama Surabaya, 2022)
Asthma is a heterogeneous chronic inflammatory condition affecting the lung. Standard treatment, a high-dose inhaled corticosteroid (ICS) and long-acting bronchodilator (LABA), effectively manages asthma in most individuals. However, 5%-10% of individuals with asthma were ineffective with those treatments. Recent RCTs suggested that Dupilumab posed potential as an add-on therapy. This systematic review aims to support the efficacy (the annualized rate of severe asthma exacerbation and increase in FEV1) and the safety of Dupilumab as an add-on therapy in uncontrolled asthma patients. We used